1997
DOI: 10.1152/ajpheart.1997.273.2.h687
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor increases microvascular permeability via a Ca(2+)-dependent pathway

Abstract: We tested the hypothesis that vascular endothelial growth factor (VEGF) increases microvascular permeability by increasing calcium influx into endothelial cells forming the vessel walls. We measured microvessel hydraulic conductivity (Lp) in isolated perfused MS-222-anesthetized frog mesenteric microvessels during perfusion with VEGF under conditions that attenuate calcium influx. VEGF increased Lp during a second successive perfusion in the same microvessel by 7.8-fold, which was not significantly different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
123
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 0 publications
3
123
0
Order By: Relevance
“…VEGF is a relatively endothelial cell-specific mitogen, promoting endothelial cell growth and survival (Alon et al, 1995;Ferrara and Davis-Smyth, 1997;Gerber et al, 1998aGerber et al, , 1998b. VEGF also causes increased vessel permeability and induction of a fenestrated phenotype, two features of VEGF bioactivity that are responsible for the increased leakiness and retinal hemorrhages seen in severe ROP (Roberts and Palade, 1995;Bates and Curry, 1997).…”
Section: Vegf and Abnormal Retinal Vascularizationmentioning
confidence: 99%
“…VEGF is a relatively endothelial cell-specific mitogen, promoting endothelial cell growth and survival (Alon et al, 1995;Ferrara and Davis-Smyth, 1997;Gerber et al, 1998aGerber et al, , 1998b. VEGF also causes increased vessel permeability and induction of a fenestrated phenotype, two features of VEGF bioactivity that are responsible for the increased leakiness and retinal hemorrhages seen in severe ROP (Roberts and Palade, 1995;Bates and Curry, 1997).…”
Section: Vegf and Abnormal Retinal Vascularizationmentioning
confidence: 99%
“…27 Vascular endothelial growth factor causes vasodilation through dose-dependent nitric oxide release from endothelial cells. 28 By increasing hydraulic conductivity, 29 inducing fenestrations across cell bodies, 30 and dissolving the tight junctions between endothelial cells by activating matrix metalloproteinases and phosphorylating both vascular endothelial cell cytoskeletal proteins 31 and the junctional proteins occludin and ZO-1, 32 VEGF breaks down the blood-retinal barrier, thereby increasing capillary leakage into the intercellular matrix. By modulating the phosphatidylinositol 3-kinase/Akt pathway, VEGF acts as a…”
Section: Vegf Synthesis and Physiologymentioning
confidence: 99%
“…9 It has been shown that VEGF also induces an increase in hydraulic conductivity of isolated microvessels and that such an effect is mediated by increased calcium influx. 10 Other studies have suggested that another important role of VEGF in the regulation of microvasclar permeability is the induction of a fenestrated phenotype in at least certain endothelial cell. 11 VEGF induces the expression of the serine proteases urokinase-and tissue-type plasminogen activators (PAs) and also PA inhibitor 1 (PAI-1) in cultured bovine microvasuclar endothelial cells.…”
mentioning
confidence: 99%